2021
DOI: 10.4013/ctc.2021.143.11
|View full text |Cite
|
Sign up to set email alerts
|

Saúde Mental, Autocuidado e Prevenção do Coronavírus em Pessoas Vivendo com HIV na Pandemia

Abstract: O objetivo foi analisar aspectos sobre a saúde mental (estresse, ansiedade e depressão), a prevenção da infecção pelo coronavírus e o autocuidado em pessoas vivendo com HIV (PVH). Participaram 148 PVH, média de idade igual a 37,9 anos, 73,6% eram homens cisgênero, acompanhadas em serviços de saúde do Distrito Federal. Trata-se de estudo on-line, com questionários sociodemográfico; médico-clínico; sobre autocuidado em HIV/aids, comportamentos preventivos da infecção pelo coronavírus, consumo de substâncias psic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
1
0
2
Order By: Relevance
“…A study developed in Uganda identified high rates of young people on ART who are sexually active and occasionally use condoms ( 25 ) . A survey conducted online with 148 people living with HIV/AIDS during the pandemic indicated that 12.2% reduced condom use during sexual intercourse ( 26 ) .…”
Section: Discussionmentioning
confidence: 99%
“…A study developed in Uganda identified high rates of young people on ART who are sexually active and occasionally use condoms ( 25 ) . A survey conducted online with 148 people living with HIV/AIDS during the pandemic indicated that 12.2% reduced condom use during sexual intercourse ( 26 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Un estudio desarrollado en Uganda identificó altas tasas de jóvenes en tratamiento antirretroviral, sexualmente activos y que hacen uso ocasional del preservativo (25) . Una investigación realizada en línea con 148 personas que vivían con el VIH/sida durante la pandemia mostró que el 12,2% redujo el uso del preservativo en las relaciones sexuales (26) .…”
Section: Abandonounclassified
“…Estudo desenvolvido na Uganda identificou altas taxas de jovens em TARV que estão sexualmente ativos e fazem o uso eventual do preservativo (25) . Pesquisa realizada de forma on-line com 148 pessoas vivendo com HIV/aids durante a pandemia apontou que 12,2% reduziram o uso de preservativos nas relações sexuais (26) .…”
Section: Análise De Dadosunclassified